Glioblastoma stem cells: lessons from the tumor hierarchy in a lethal cancer - Gimple, Ryan C; Bhargava, Shruti; Dixit, Deobrat; Rich, Jeremy N (Genes & development, 2019)
Glioblastoma ranks among the most lethal of all human cancers. Glioblastomas display striking cellular heterogeneity, with stem-like glioblastoma stem cells (GSCs) at the apex. Although the original identification of GSCs dates back more than a decade, the purification and characterization of GSCs remains challenging. Despite these challenges, the evidence that GSCs play important roles in tumor growth and response to therapy has grown. Like normal stem cells, GSCs are functionally defined and distinguished from their differentiated tumor progeny at core transcriptional, epigenetic, and metabolic regulatory levels, suggesting that no single therapeutic modality will be universally effective against a heterogenous GSC population. Glioblastomas induce a systemic immunosuppression with mixed responses to oncoimmunologic modalities, suggesting the potential for augmentation of response with a deeper consideration of GSCs. Unfortunately, the GSC literature has been complicated by frequent use of inferior cell lines and a lack of proper functional analyses. Collectively, glioblastoma offers a reliable cancer to study cancer stem cells to better model the human disease and inform improved biologic understanding and design of novel therapeutics.